1219 Colorado - Spaw, Christopher Alan (Kansas State University, 2005)
1219 Colorado is the documentation of the nonlinear process of design as it applies to the reconfiguration of a residential dwelling. This process is illustrated through a collection of sketches, design drawings, construction documents and images produced from 1999 to 2005. 1219 Colorado investigates materiality the physical substance of architecture, as well as the nature of thoughtful connection physical and theoretical through the process of making. The need to build, to make, to design, and explore is what drives the process. While the space of architecture is most often designed and perceived as lines on paper, it is through the making of physical models that the creative act of discovery reveals its greatest potential. The process explores the design of a model constructed at full-scale. No longer representational, the study is the product; the materials and methods are genuine. This process differs from the process of building in that the intention is no longer to construct only that which is designed. Rather the challenge is to explore beyond the design, reveal new possibilities, refine design decisions, and most importantly to take advantage of unforeseen opportunities that are revealed through the act of making. The scope of the task expanded periodically as a function of increasing knowledge of construction, declining acceptance of the quality of the existing condition and in order to accommodate an evolving set of programmatic requirements. To date the construct has under gone no less than three different design schemes, and a fourth will follow as the process continues to be refined and reconsidered. The project continues to evolve, grow, and change directions. 1219 Colorado explores design is not a linear process. Architecture is not always pretty.
Keywords: Architecture (0729); Full-scale model